2021
DOI: 10.1038/s41419-021-04052-5
|View full text |Cite|
|
Sign up to set email alerts
|

C-type lectin receptor Dectin3 deficiency balances the accumulation and function of FoxO1-mediated LOX-1+ M-MDSCs in relieving lupus-like symptoms

Abstract: Recent studies indicate that Toll-like receptors (TLRs) and C-type lectin receptors (CLRs) can function as the signal of pattern recognition receptors, which play a pivotal role in the pathogenesis of the autoimmune disease. Systemic lupus erythematosus (SLE) is a classic autoimmune disease. Previous reports mainly focused on the potential role of TLRs in regulating the development of SLE, but little is known about the role of CLRs in the progression of SLE. Our previous studies showed that the inflammation-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…As predicted by the non-inflammatory environment, the IGF1R lo CD14 + cells produced higher levels of IL10 and IL1β as judged by RNA-seq and by protein cytokine levels in cell culture supernatants ( Figures 4C, D ), a sign of M2-type macrophages. In addition to cytokines, IGF1R lo CD14 + cells expressed higher levels of MHCII receptors HLA-DQA1, HLA-DPA1 and HLA-DRB1, and in C-type lectin binding receptors including the macrophage scavenger receptor 1 (MSR1) and the mannose receptor 1 (MRC1) directly interacting with T cells ( 47 ) ( Figure 4D ), and CLEC6A/DCIR2, CLEC4E/MINCLE, CLEC5A/MDL1, CLEC12A/MICL, CLEC4A/DCIR ( Figure 4E ) essential for immunoregulation of T and B cell function ( 48 51 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As predicted by the non-inflammatory environment, the IGF1R lo CD14 + cells produced higher levels of IL10 and IL1β as judged by RNA-seq and by protein cytokine levels in cell culture supernatants ( Figures 4C, D ), a sign of M2-type macrophages. In addition to cytokines, IGF1R lo CD14 + cells expressed higher levels of MHCII receptors HLA-DQA1, HLA-DPA1 and HLA-DRB1, and in C-type lectin binding receptors including the macrophage scavenger receptor 1 (MSR1) and the mannose receptor 1 (MRC1) directly interacting with T cells ( 47 ) ( Figure 4D ), and CLEC6A/DCIR2, CLEC4E/MINCLE, CLEC5A/MDL1, CLEC12A/MICL, CLEC4A/DCIR ( Figure 4E ) essential for immunoregulation of T and B cell function ( 48 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our findings, FOXO1 deficient peripheral B cells have been shown to express low levels of CD62L and to fail class-switch recombination ( 41 , 60 ). Additionally, FOXO1 silencing promoted monocyte expansion, which was concomitant with exacerbation of SLE-like autoimmunity ( 51 ). Analogously, IGF1R lo CD14 + cells from RA patients had low expression of FOXO family proteins, which coincided with a higher frequency of autoantibody production in those patients, which leads us to believe that IGF1R dependent activity of FOXO in APC was an important mechanism counteracting break of immunological tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to deteriorating experimental autoimmune encephalomyelitis ( 110 ) and systemic lupus erythematosus ( 111 ), Dectin-3 was initially found a limited role in regulating intestinal immunity ( 112 ), while later research revealed that Dectin-3 was also significant in intestinal homeostasis through interplaying with commensal fungi. The deficiency of Dectin-3 leads to more susceptibility to DSS-induced mouse colitis, with an obviously increase of specific fungal burden and microbial translocation, especially a common commensal Candida tropicalis ( 113 ).…”
Section: The Role Of Clrs In the Interplay Between Fungal Microbiota ...mentioning
confidence: 99%
“…One is similar to what we have discussed above: the regulation of the production of certain functional cytokines, such as IFN-γ, TGF-β, and IL-27, could increase PD-L1 mRNA expression ( 104 ), which may partly explain the mechanism of PD-L1 upregulation in the regulation of fungi–CLR interaction. The other possible direction is from the expression characteristics of CLRs, which are mainly expressed in innate immune cells, such as macrophages, dendritic cells, monocytes, and MDSCs ( 105 , 106 ). It is worth noting that, in addition to tumor cells, these myeloid-derived innate immune cells can also express PD-L1 in the tumor microenvironment ( 107 , 108 ).…”
Section: Justification Of the Hypothesismentioning
confidence: 99%